Surgical treatment of retropharyngeal lipofibroma complicated by compression syndrome - A. S. Kuzmichev; A. L. Akinchev; A. N. Savin; V. I. Lomakin; D. V. Makharoblisvili (Вестник хирургии имени И.И. Грекова)
The article is presented the description of rare clinical observation of the patient with pharyngeal lipofibroma complicated by compression syndrome, accompanied by impaired swallowing and breathing. The patient was successfully operated on with cervical access.